Finite element analysis of stress and free vibration of beams under elastoplastic loading conditions using ANSYS finite element software - Ng, Celeste (Nanyang Technological University, 2024)
Beams are essential structural elements that are widely used in different engineering industries such as aerospace and civil engineering. Beams are used to withstand the weight of ceilings and roofs of a building. As such, beams are often subjected to many kinds of loads such as bending moments, shear forces and axial loads. These loads often play a critical role in ensuring structure integrity in these infrastructures, and thus it is very important to have some form of analytical tool to be able understand the behaviours of these loads and their potential impact they will cause. Finite element analysis (FEA) is a powerful tool that is commonly used to conduct numerical calculations and load simulations to access the behaviour and the impacts of such loads. In this project, the finite element software ANSYS Mechanical APDL is used to conduct static and free vibration analysis of beams undergoing plastic deformation and to understand the effects of plastic deformation on the natural frequencies. From the results of static analysis, it is discovered that as the load applied increases, the stress profile of the beam will be fully elastic before yielding. However, upon yielding, plastic deformation occurs and forms an elastic core between the top and bottom surface of the beam. The stress distribution within the elastic core is linear, whereas the stress value remains constant at yield stress in the plastic region. After yielding, the plastic regions continue to grow with increasing load. At the same time, the elastic core decreases accordingly. As for the results from free vibration analysis, there is minimal change in the natural frequencies with increasing load before yielding. After yielding takes place, there is a significant decrease in natural frequencies with an increase in load. Another interesting observation is that at the start of unloading, a rapid increase in natural frequency back to the initial starting natural frequency can be seen. Following that, the natural frequency remains constant at this frequency until the beam is fully unloaded.